Subject identification via ECG fiducial-based systems: Influence of the type of QT interval correction. Issue 3 (October 2015) - Gargiulo, Francesco; Fratini, Antonio; Sansone, Mario; Sansone, Carlo
<x xml:space="preserve">Abstract</x> Highlights Electrocardiography (ECG) has been recently proposed as biometric trait for identification purposes. The influence of the QT interval correction method on the performance of ECG-based identification systems is analyzed. ECG signals were collected from the Physionet open access database. A public domain software was used for fiducial points detection. Results suggested that QT correction is always required to improve the performance.